2001
DOI: 10.1046/j.1365-2265.2001.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the number and impact of stressful life events and the onset of Graves' disease and toxic nodular goitre

Abstract: These results suggest that SLEs are a precipitating factor of the onset of GD. We also demonstrated that SLEs do not seem to have any conclusive relationship with the onset of TNG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 15 publications
3
33
0
5
Order By: Relevance
“…In a recent prospective study, it was shown that four personality traits (hypochondria, depression, paranoia and mental fatigue) were positively related to the relapse rate after antithyroid drugs in Graves' disease, and that stressful life events correlated with the titer of thyroid-stimulating hormone (TSH)-receptor antibodies (67). Another casecontrol study found that Graves' disease patients had had a significantly greater number of stressful life events than patients with toxic nodular goiter or controls (the latter two groups were not different from each other in terms of stressful life events) (68).…”
Section: Stressmentioning
confidence: 99%
“…In a recent prospective study, it was shown that four personality traits (hypochondria, depression, paranoia and mental fatigue) were positively related to the relapse rate after antithyroid drugs in Graves' disease, and that stressful life events correlated with the titer of thyroid-stimulating hormone (TSH)-receptor antibodies (67). Another casecontrol study found that Graves' disease patients had had a significantly greater number of stressful life events than patients with toxic nodular goiter or controls (the latter two groups were not different from each other in terms of stressful life events) (68).…”
Section: Stressmentioning
confidence: 99%
“…Some of the publications reported the presence of stress in 62 or 85% of the cases, or even in all cases (review in (7)). A review of the literature including seven case-control studies has highlighted the preexistence of a 'negative' stressful event in patients with Graves' disease (8,9,10,11,12,13,14,15). However, one can criticize the principle of case-control studies: it is difficult to assess the effect of a given stressful event in different individuals; the validity of filling out a questionnaire may be limited in an emotional context, the actual date of the onset of the disease is difficult to specify and nothing proves that it occurred after the stressful event (8).…”
Section: Epidemiological Data On Stress and Graves' Diseasementioning
confidence: 99%
“…The first event is an inborn genetic susceptibility (reviewed in Tomer and Davies 4 ) followed by a second event that is an encounter with an external trigger such as infection (for a review see Tomer and Davies 5 ) or stress. 6 As a result, thyroid-specific T cells become activated and infiltrate the thyroid. The thyroid infiltrating T cells activate B cells to secrete TSHR-stimulating antibodies that induce proliferation of thyrocytes, and production of excess thyroid hormones resulting in hyperthyroidism and goiter (reviewed in Davies 3 ).…”
Section: Introductionmentioning
confidence: 99%